PERSON DEXIS IN FROZEN MOVIE SCRIPT BY SORROW - Ayu Meita Puteri Siregar (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
This study aims at describing the types of personal deixis and finding the reference of personal deixis. The object to be analyzed is personal deixis in the form of words. The data in this study was obtained from Frozen Movie Script was taken from dialogue 0:03:39.94 to dialogue 0:11:12.82. The type of the research is descriptive qualitative research. In clarifying the types of personal deixis the researcher uses pragmatics analysis especially deixis theory. Then, the technique of analyzing data are finding the types of personal deixis used in Frozen movie script, describing the reference of the use of personal deixis in movie script of Frozen, drawing the conclusion and suggestion based on the data analysis. The research finding of the study shows that there are three types of personal deixis first personal deixis, second personal deixis and third personal deixis and three kinds of the reference on Frozen Movie include that reference that refers to first person, the reference which refers to second person and the reference which refers to third person. The data of this research consists of 85 personal deixis include that 43 data type of first personal deixis, 22 data type of second personal deixis and 12 data type of third personal deixis.